Natural history of aortic valve endocarditis in rats. - Héraïef, E (1982)
Sterile aortic vegetations were produced in rats by introducing a polyethylene catheter through the right carotid artery. The catheter was either left in place throughout the experiments or removed before bacterial challenge. Bacterial endocarditis was uniformly produced by intravenous injection of 10(7) colony-forming units of Staphylococcus aureus or Streptococcus intermedius, whether the catheter was left in place or removed. However, in rats with the catheter left in place, bacterial multiplication within the vegetations with both strains was accelerated, and mortality from Staphylococcus aureus infection was increased. Using 10(7) colony-forming units of serum-resistant Escherichia coli as a test microorganism, we found a marked difference in the production of endocarditis depending upon whether the catheter was left in place or removed before injection; only those animals infected with the catheter in place developed infection. From these experiments in rats, it was evident that the presence of a foreign body has a considerable influence on the ability of bacteria to grow within an intravascular vegetation. In addition, a striking difference in the virulence of the three strains studied was established; Staphylococcus aureus was the most, and E. coli the least, pathogenic.